Sleep Duration/Quality With Health Outcomes: An Umbrella Review of Meta-Analyses of Prospective Studies - Gao, Chang; Guo, Jiao; Gong, Ting-Ting; Lv, Jia-Le; Li, Xin-Yu; Liu, Fang-Hua; Zhang, Meng; Shan, Yi-Tong; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Medicine, 2022)
Background To quantitatively evaluate the evidence of duration and quality of sleep as measured by multiple health outcomes. Methods This review is registered with PROSPERO, number CRD42021235587. We systematically searched three databases from inception until November 15, 2020. For each meta-analysis, the summary effect size using fixed and random effects models, the 95% confidence interval, and the 95% prediction interval were assessed; heterogeneity, evidence of small-study effects, and excess significance bias were also estimated. According to the above metrics, we evaluated the credibility of each association. Results A total of 85 meta-analyses with 36 health outcomes were included in the study. We observed highly suggestive evidence for an association between long sleep and an increased risk of all-cause mortality. Moreover, suggestive evidence supported the associations between long sleep and 5 increased risk of health outcomes (stroke, dyslipidaemia, mortality of coronary heart disease, stroke mortality, and the development or death of stroke); short sleep and increased risk of overweight and/or obesity; poor sleep quality and increased risk of diabetes mellitus and gestational diabetes mellitus. Conclusions Only the evidence of the association of long sleep with an increased risk of all-cause mortality was graded as highly suggestive. Additional studies are needed to be conducted. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021235587